Investigating the Integrating of ICT in English Language Learning: A Case Study at SMP Negeri 1 Panca Rijang - Isumarni Isumarni; Muhammad Hanafi; Sam Hermansyah; Aliyah Aliyah; Nia Ramadhani; Dewi Anjasari; Rahmah Nurhalisah Mulyadi (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study investigates the integration of Information and Communication Technology (ICT) in English language learning at SMP Negeri 1 Panca Rijang. The research is driven by the increasing demand for innovative teaching methods in the 21st century, where digital tools are considered essential to support effective learning environments. A qualitative case study approach was employed, involving eighth-grade students as participants. Data were gathered through classroom observations, semi-structured interviews, and questionnaires in order to capture both teachers’ and students’ perspectives on ICT integration. The findings indicate that ICT integration provides multiple benefits in English learning. First, it enhances classroom interaction by promoting active student participation through the use of multimedia presentations, online quizzes, and language learning applications. Second, it fosters student motivation by making lessons more engaging, enjoyable, and relevant to real-life communication. Third, ICT offers authentic learning experiences by exposing students to original English materials such as videos, digital texts, and interactive exercises. However, the research also identified several challenges in implementing ICT. These include limited school facilities, unequal access to digital devices, unstable internet connectivity, and the need for teachers to develop stronger digital literacy and pedagogical skills for technology-enhanced instruction. Despite these challenges, the overall results suggest that ICT, when appropriately designed and systematically integrated, significantly improves the quality of English language teaching and learning at the junior high school level.